Toward a Humane Death with Dementia - Dresser, Rebecca (The Hastings Center report, 2014)
In this issue, Paul Menzel and M. Colette Chandler-Cramer propose a novel advance directive. Besides giving competent people the opportunity to refuse future life-prolonging medical interventions, they say, advance directives should give people the opportunity to refuse ordinary food and water if they later experience severe dementia. This proposal is both appealing and unsettling. It is appealing because it offers some relief to people seeking to avoid the prolonged decline and extreme incapacity they have witnessed in relatives and friends with advanced dementia. But does it sufficiently protect patients? Menzel and Chandler-Cramer want to empower competent persons to impose potential discomfort and distress on a later self who cannot understand the reasons for that choice. In this situation, the price of respecting autonomy is paid by a frail incapacitated patient who has no idea why food and water are no longer offered to her.